A four-year record of UK′37- and TEX86-derived sea surface temperature estimates from sinking particles in the filamentous upwelling region off Cape Blanc, Mauritania. (March 2015) - Mollenhauer, Gesine; Basse, Andreas; Kim, Jung-Hyun; Sinninghe Damsté, Jaap S.; Fischer, Gerhard
Abstract: Lipid biomarker records from sinking particles collected by sediment traps can be used to study the seasonality of biomarker production as well as processes of particle formation and settling, ultimately leading to the preservation of the biomarkers in sediments. Here we present records of the biomarker indices U 37 K ′ based on alkenones and TEX86 based on isoprenoid glycerol dialkyl glycerol tetraethers (GDGTs), both used for the reconstruction of sea surface temperatures (SST). These records were obtained from sinking particles collected using a sediment trap moored in the filamentous upwelling zone off Cape Blanc, Mauritania, at approximately 1300 water depth during a four-year time interval between 2003 and 2007, and supplemented by U 37 K ′ and TEX86 determined on suspended particulate matter collected from surface waters in the study area. Mass and lipid fluxes are highest during peak upwelling periods between October and June. The alkenone and GDGT records both display pronounced seasonal variability. Sinking velocities calculated from the time lag between measured SST maxima and minima and corresponding index maxima and minima in the trap samples are higher for particles containing alkenones (14–59 m d −1 ) than for GDGTs (9–17 m d −1 ). It is suggested that GDGTs are predominantly exported from shallow waters by incorporation in opal-rich particles. SST estimates based on the U 37 K ′ index correspond to the amplitude observed fluctuations in SST during the study period. Temperature estimates based on TEX86 show smaller seasonal amplitudes, which can be explained by either predominant production of GDGTs during the warm season, or a contribution of GDGTs exported from deep waters, which are in this region known to carry GDGTs in a distribution that translates to a high TEX86 signal. Highlights: In the Cape Blanc filament, UK׳37 and TEX86 records show seasonal temperature changes. Export of lipids is delayed, and the delay is longer for archaeal lipids than for alkenones. TEX86-temperature variations have a smaller amplitude than SST, consistent with Thaumarchaeota production during summer or subsurface export.